A Qualitative Study of Specialized Clinical Nurses' Perceptions of Good Care in Practice. Issue 5 (September 2018) - Valizadeh, Leila; Zamanzadeh, Vahid; Rassouli, Maryam; Ghahramanian, Akram; M. Archibald, Mandy; Asghari, Elnaz
Abstract : Purpose/Aims: The aim of this study was to explore specialized clinical nurses' (SCNs') perceptions of "good care" through descriptions of actual care experiences. Design: We used a qualitative design with a conventional content analysis approach. Methods: We conducted semistructured interviews with 24 SCNs. These nurses have passed specialized clinical courses, are master's or bachelor's degree prepared, have additional course work beyond the bachelor degree, and practice with an expanded scope of responsibility. The participants were purposively sampled from general and specialty hospitals, and 6 field notes were collected. Results: We identified 3 overarching themes to classify the findings: patient-centered care, knowledge-based care, and skillful practice. Participants regarded these 3 components as interdependent and related, which we conceptualize as 3 sides of an equilateral triangle termed the Good Care Triangle. Conclusions: The Good Care Triangle provides a heuristic approach to consider professional standards from the perspectives of SCNs and provides needed insight into SCNs' perspectives on the fundamental yet underexplored concept of good care. Clinical leaders can consider how the 3 themes identified are reflected and enacted in the care practices of SCNs. Future research could examine the utility of the Good Care Triangle in guiding nursing education and evaluating SCNs' perspectives of the care that they are providing.